2022
DOI: 10.1002/rsa.21106
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Ramsey properties of random graphs involving cliques and cycles

Abstract: We prove that for every , r ≥ 3, there exists c > 0 such that for p ≤ cn −1/m 2 (Kr ,C ) , with high probability there is a 2-edge-colouring of the random graph Gn,p with no monochromatic copy of Kr of the first colour and no monochromatic copy of C of the second colour. This is a progress on a conjecture of Kohayakawa and Kreuter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…We then apply a new procedure Extend which attaches either a k-graph L ∈ L G ′ or R ∈ R G ′ that contains e to F i . As in Case 1, because the condition in line 6 of Asym-Edge-Col-Bε fails, G ′ ∈ C. 22 We now show that the number of edges of F i increases by at least one in each iteration of the while-loop and that Grow-Alt operates as desired with a result analogous to Claim 7.1.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…We then apply a new procedure Extend which attaches either a k-graph L ∈ L G ′ or R ∈ R G ′ that contains e to F i . As in Case 1, because the condition in line 6 of Asym-Edge-Col-Bε fails, G ′ ∈ C. 22 We now show that the number of edges of F i increases by at least one in each iteration of the while-loop and that Grow-Alt operates as desired with a result analogous to Claim 7.1.…”
mentioning
confidence: 56%
“…This is achieved in the paper of Marciniszyn, Skokan, Spöhel and Steger [23] which deals with the case when H 1 and H 2 are both cliques (and not both K 3 ), albeit with different methods. In [18] and [22], which deal with the cases when H 1 and H 2 are both cycles and H 1 and H 2 are a clique and a cycle, respectively, the authors of both papers show implicitly that B(H 1 , H 2 ) = ∅. Let us also remark that in [23], it is implicitly shown that B(H 1 , H 2 ) with each H i a clique, is non-empty only when H 2 = K 3 or H 1 = H 2 = K 4 , and moreover, | B(H 1 , H 2 )| ≤ 3 in each case.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when H is a tree the threshold is p = 1∕N. A corresponding result for hypergraphs was obtained by Friedgut, Rödl, and Schacht [13] and independently by Conlon and Gowers [8], and the 1-statement of an asymmetric version (conjectured by Kohayakawa and Kreuter [20] in 1997) was recently proved by Mousset, Nenadov, and Samotij [31] (see [17,20,25,27] for progress in the 0-statement).…”
Section: Introductionmentioning
confidence: 87%